Regression of retinal capillaries following N‐methyl‐D‐aspartate‐induced neurotoxicity in the neonatal rat retina. Issue 2 (3rd October 2014) - Asano, Daiki; Nakahara, Tsutomu; Mori, Asami; Sakamoto, Kenji; Ishii, Kunio
<x xml:space="preserve">Abstract</x> Degeneration of retinal capillaries occurs following N‐methyl‐D‐aspartate (NMDA)‐induced retinal neurotoxicity, and the degree of capillary degeneration decreases in an age‐dependent manner. To determine the role of vascular endothelial growth factor (VEGF) in the high susceptibility of capillaries to neuronal damage during the early postnatal stage, this study compares the vascular regression patterns between NMDA‐treated retinas and retinas treated with N‐[2‐chloro‐4‐{(6, 7‐dimethoxy‐4‐quinazolinyl)oxy}phenyl]‐N′‐propylurea (KRN633), a VEGF receptor tyrosine kinase inhibitor, in neonatal rats. Two days after a single intravitreal injection of NMDA (200 nmol/eye) on postnatal day (P) 7, substantial retinal neuron loss and delayed expansion of the retinal vascular bed were observed. The reduction in the capillary density in the central retina reached statistical significance 4 days after NMDA treatment. In retinas of rats injected subcutaneously with KRN633 (10 mg/kg) on P7 and P8, simplified vasculature attributable to capillary regression and prevention of endothelial cell growth were seen on P9, whereas no visible changes in the morphology of the retinal layers were observed. The degree of capillary degeneration in NMDA‐treated retinas was less than that in KRN633‐treated retinas. No apparent changes in immunoreactivities for VEGF were found 2 days after NMDA treatment. These results indicate that neuronal cell loss in the retina precedes retinal capillary degeneration following NMDA treatment, and VEGF‐dependent immature capillaries might be more susceptible to NMDA‐induced neuronal damage. © 2014 Wiley Periodicals, Inc.